Penerapan Metode Agglomerative Hierarchical Clustering untuk Klasifikasi Kabupaten/Kota di Propinsi Jawa Timur Berdasarkan Kualitas Pelayanan Keluarga Berencana - Fadliana, Alfi; Rozi, Fachrur (CAUCHY, 2015)
Agglomerative hierarchical clustering methods is cluster analysis method whose primary purpose is to group objects based on its characteristics, it begins with the individual objects until the objects are fused into a single cluster. Agglomerative hierarchical clustering methods are divided into single linkage, complete linkage, average linkage, and ward. This research compared the four agglomerative hierarchical clustering methods in order to get the best cluster solution in the case of the classification of regencies/cities in East Java province based on the quality of â€œKeluarga Berencanaâ€ (KB) services. The results of this research showed that based on calculation of cophenetic correlation coefficient, the best cluster solution is produced by average linkage method. This method obtained four clusters with the different characteristics. Cluster 1 has an â€œextremely bad conditionâ€ on the qualification of KB clinics and the competence of KB service personnel. Cluster 2 has a â€œgood conditionâ€ on the qualification of KB clinics and â€œbad conditionâ€ on the competence of KB service personnel. Cluster 3 has a â€œbad conditionâ€ on the qualification of KB clinics and â€œmedium conditionâ€ on the competence of KB service personnel. Cluster 4 have a â€œmedium conditionâ€ on the qualification of KB clinics and a â€œgood conditionâ€ on the competence of KB service personnel